Micro porous carbon spring based on femtosecond laser micro-nano machining and preparation method thereof
Through femtosecond laser micro-nano processing technology, laser parameters are controlled to induce the growth of spiral-structured micro porous carbon springs on the surface of the polyimide film, solving the problem of low efficiency in the preparation of complex structure micro-full carbon devices in the prior art, and achieving efficient preparation of micro porous carbon springs suitable for mass production.
Patent Information
- Application Number
- CN202411469589.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The prior art is difficult to efficiently prepare three-dimensional micro-full carbon devices with complex structures, such as spiral carbon springs, and the 3D printing method is inefficient and expensive, and it is not suitable for large-scale production.
Femtosecond laser micro-nano processing technology is used to induce the growth of microporous carbon springs with opposite chiral structures on the surface of the polyimide film by controlling laser parameters.
It realizes the rapid and convenient preparation of micro porous carbon springs, is suitable for mass production, and has good electrical conductivity, mechanical properties and environmental stability.
Smart Images

Figure CN119772369A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of femtosecond laser micro-nano processing, and in particular to a micro porous carbon spring based on femtosecond laser micro-nano processing and a preparation method thereof. Background Art
[0002] In nature, the spiral structure is one of the most common three-dimensional structures. From macroscopic to microscopic, from overall to local, spiral structures can be found in almost all substances, such as DNA, spirochete microorganisms, conchs, vines, etc. In human society, devices and parts with spiral structures are also everywhere, such as springs, electromagnetic coils, screws, etc. This special structure can give the device unique properties, making it suitable for various special occasions. With the development of human society, devices are increasingly inclined to miniaturization and integration, and the simple and efficient preparation of various complex three-dimensional micro devices has received more and more attention.
[0003] Porous carbon materials have the advantages of high specific surface area, high electrical conductivity, high chemical stability against acid and alkali corrosion, gas-liquid permeability, adjustable pore structure, and good electromagnetic wave absorption. They have shown great application prospects in the fields of energy storage and conversion, catalysis, adsorption and separation. However, it is still a difficult problem to prepare three-dimensional micro all-carbon devices with complex structures, such as the helical carbon spring, which is one of the basic components of carbon-based devices. Currently, micro carbon springs are mainly prepared by 3D printing, which requires expensive additive manufacturing equipment and special graphite inks. In addition, due to the bottom-up layer-by-layer printing method, the processing efficiency is extremely low and it is not suitable for large-scale mass production. Summary of the invention
[0004] The present invention provides a micro porous carbon spring based on femtosecond laser micro-nano processing and a preparation method thereof. The present invention utilizes femtosecond laser micro-nano processing technology to control laser parameters to finally induce a pair of micro porous carbon springs with opposite chirality to grow on the surface of a polyimide film. This preparation method is simple and convenient and suitable for mass production. The produced micro porous carbon spring has good electrical conductivity, mechanical properties and environmental stability. It is specifically achieved through the following technologies.
[0005] The first aspect of the present invention provides a method for preparing a micro porous carbon spring based on femtosecond laser micro-nano processing, comprising the following steps: fixing a polyimide film on a glass slide, and fixing the glass slide on a stage; adjusting laser parameters, focusing the laser beam on the surface of the polyimide film for scanning, and obtaining the micro porous carbon spring; the laser parameters are a laser power of 500 mW-4000 mW and a scanning speed of 1-10 mm / s.
[0006] The preparation method of the above-mentioned micro porous carbon spring provided by the present invention is to focus the laser on the surface of the polyimide film, use femtosecond laser direct writing technology, adjust the processing parameters to control the thermal accumulation effect during the femtosecond laser direct writing process, and finally induce the growth of a pair of micro porous carbon springs with opposite chirality on the surface of the polyimide film.
[0007] The reaction process and working principle of the above preparation method are specifically as follows:
[0008] (1) Under the action of high repetition rate and high pulse energy femtosecond laser pulses, polyimide absorbs laser energy through multiphoton absorption, thereby undergoing multiphoton ionization and ablation.
[0009] (2) The ablation process generates strong heat accumulation, and the accumulated heat diffuses to both ends of the ablation area to form a heat-affected zone. However, polyimide has the characteristics of low thermal conductivity, and the energy distribution characteristics of the Gaussian laser lead to highly localized heat accumulation.
[0010] (3) There is an extremely high temperature gradient in the heat-affected zone, which causes the area close to the ablation groove to begin to graphitize and form graphite carbon with high crystallinity, while the area far from the ablation groove produces amorphous carbon with low crystallinity. At the same time, different temperatures lead to different degrees of pyrolysis, and the amount and rate of gas release are also different; the closer the area is to the ablation center, the more gas is released and the more pores are generated.
[0011] When the stress generated by the local high pressure caused by gas accumulation is greater than the bonding force between the induced carbon structure and the substrate, the carbon wires (graphite carbon and amorphous carbon) will be quickly peeled off from the polyimide substrate. In addition, since the carbon wires on the left and right sides of the ablation groove are subjected to opposite centripetal forces, when combined with the original peeling trajectory during the laser scanning process, a pair of chirally symmetrical micro porous carbon springs are generated.
[0012] Laser parameters have a significant impact on the three-dimensional performance (diameter, thickness, width and pitch) of the micro porous carbon spring. The present invention has found that with the increase of laser power, the width, thickness, diameter and pitch of the porous carbon spring gradually increase; with the increase of scanning speed, the width, thickness, diameter and pitch of the porous carbon spring gradually decrease. Based on the above reaction process and mechanism of action, in order to achieve effective regulation of the thermal accumulation effect and ensure that a pair of micro porous carbon springs with opposite chirality spiral structures grow on the surface of the polyimide film, it is necessary to pre-debug the femtosecond laser processing system to select appropriate laser parameters.
[0013] Furthermore, the numerical aperture NA of the objective lens is 0.14, and the magnification is 5 times; the method for debugging the laser parameters is as follows: the fixed parameters of the laser beam after focusing through the objective lens are designed to be a laser wavelength of 1028 nm, a pulse width of 190 fs, and a repetition frequency of 200 kHz.
[0014] Furthermore, the thickness of the polyimide film is 50-200 μm.
[0015] Furthermore, the thickness of the polyimide film is 100 μm.
[0016] The second aspect of the present invention provides a micro porous carbon spring prepared by any one of the above-mentioned preparation methods.
[0017] The third aspect of the present invention provides an application of the above-mentioned micro porous carbon spring for manufacturing micro mechanical equipment and micro electronic components.
[0018] Since the micro porous carbon spring prepared by the present invention has good electrical conductivity, mechanical strength (mainly tensile properties) and environmental stability, it can be used as a component of micro-mechanical and micro-electronic equipment, and is widely used in micro-mechanical equipment (such as micro-robots, etc.), micro-electronic components (such as micro-resistance wires, etc.) and other fields.
[0019] In a fourth aspect of the present invention, a micro-nano processing system for preparing a micro porous carbon spring is provided, the micro-nano processing system comprising a pulse laser, an energy attenuator, a first reflector, a polarization rotator, a second reflector, a third reflector, a first semi-transparent semi-reflective reflector, a fourth reflector, a focusing objective lens, a stage and a control component; a three-dimensional moving mechanism is provided below the stage, and the three-dimensional moving mechanism is electrically connected to the control component;
[0020] The laser light path emitted by the pulse laser passes through the energy attenuator, the first reflector, the polarization rotation mirror, the second reflector, the third reflector, the first semi-transparent and semi-reflective mirror, the second semi-transparent and semi-reflective mirror, the fourth reflector and the focusing objective lens in sequence, and is irradiated onto the stage.
[0021] Furthermore, the micro-nano processing system also includes a shooting component, a second semi-transparent and semi-reflective mirror and a light source; the second semi-transparent and semi-reflective mirror is located between the first semi-transparent and semi-reflective mirror and the lens of the shooting component, and the light source is facing the second semi-transparent and semi-reflective mirror.
[0022] The preparation method of the micro porous carbon spring provided by the present invention is generally carried out on a micro-nano processing system. The present invention provides a specific structure of the above-mentioned micro-nano processing system. In the above-mentioned micro-nano processing system, a polyimide film is fixed on the surface of a glass slide, and then the glass slide is fixed on a stage. An energy attenuator is used to adjust the power of the laser, and the femtosecond laser with adjusted parameters is introduced into the system. The laser beam is focused on the surface of the polyimide film, and the movement of the stage is controlled by the control component to realize femtosecond laser scanning.
[0023] Optionally, the glass slide may be fixed by negative pressure suction or the like, for example, by providing an air pump on the stage.
[0024] If necessary, the micro-nano processing system can also be provided with a photographing component to observe the entire preparation process of the micro porous carbon spring in real time.
[0025] In a fifth aspect of the present invention, a micro-nano processing parameter database for preparing a micro porous carbon spring is provided, wherein the micro-nano processing parameter database is constructed by setting different laser parameters to obtain the corresponding micro porous carbon spring, and testing the diameter, thickness, width and pitch of the micro porous carbon spring. In practical application, appropriate processing parameters can be selected for processing according to the actual size requirements of the performance parameters.
[0026] Compared with the prior art, the present invention is beneficial in that:
[0027] 1. The present invention provides a method for preparing a micro porous carbon spring. With this method, a single laser scan can simultaneously induce a pair of micro porous carbon springs with opposite chirality in the spiral direction. This method is fast, convenient, repeatable, and suitable for simple and efficient mass production. The thickness, width, pitch and diameter of the micro porous carbon spring, as well as related properties (conductivity, mechanical strength, environmental stability, etc.) can be precisely controlled by adjusting local heat.
[0028] 2. The micro porous carbon spring prepared by the present invention is a full carbon structure, with a length of up to centimeters and a good loose porous microstructure.
[0029] When the laser power is 2000 mW and the scanning speed is 5 mm / s, the prepared micro porous carbon spring has good electrical conductivity and the line resistance is lower than 1.68 kΩ / mm; it has good mechanical strength. Under a steady external force, the micro porous carbon spring can be stretched from 26.1 mm in its natural state to a maximum of 43.5 mm, and the strain reaches 66.7%, which shows that the micro porous carbon spring has certain stretchability and can store a certain elastic potential energy. Its elastic constant is about 1.2 N / m; it has good environmental stability, and the relative conductivity changes in various gas environments are less than 1%.
[0030] 3. The present invention also provides a micro porous carbon spring that can be widely used in multiple industries such as micro-mechanics and micro-electronics technology, and is specifically used for assembling and manufacturing micro-springs, micro-robots, and micro-resistance wires.
[0031] 4. The present invention also provides a micro-nano processing system based on the preparation method of the micro porous carbon spring, and a micro-nano processing parameter database. This system can be used to study the influence of laser parameters, polyimide film thickness, scanning speed and other parameters on the width, thickness, diameter, pitch and other structural data of the micro porous carbon spring, as well as the influence on the conductivity, mechanical properties and stability of the micro porous carbon spring, and these data are correlated to form a micro-nano processing parameter database for preparing micro porous carbon springs. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A structural schematic diagram and optical path diagram of the micro-nano processing system provided by the present invention;
[0033] Figure 2 Product photo of a single micro porous carbon spring.
[0034] Figure 3 This is the relationship between the growth range of micro porous carbon springs and the femtosecond laser scanning speed and laser power.
[0035] Figure 4 This is a SEM image of a micro porous carbon spring. Figure 4 a is the SEM image of the micro porous carbon spring. Figure 4 b is the SEM image of the inner surface of the micro porous carbon spring. Figure 4 c is the SEM image of the outer surface of the micro porous carbon spring.
[0036] Figure 5 This is the element distribution map (EDS mapping) of the micro porous carbon spring.
[0037] Figure 6 This is the Raman spectrum of the micro porous carbon spring.
[0038] Figure 7-10 These are the corresponding relationship diagrams of the width, thickness, diameter and pitch of the micro porous carbon spring and the laser power.
[0039] Figure 11-14 These are the corresponding relationship diagrams of the width, thickness, diameter and pitch of the micro porous carbon spring and the scanning speed.
[0040] Fig.15 A side view of the stretched micro porous carbon spring.
[0041] Fig.16Actual pictures of micro porous carbon springs induced by polyimide films of different thicknesses.
[0042] Fig.17 This is the conductivity test diagram of the micro porous carbon spring.
[0043] Figure 1 The figures in the figure are as follows: 1. pulse laser; 2. energy attenuator; 3. first reflector; 4. polarization rotation mirror; 5. second reflector; 6. third reflector; 7. first semi-transparent and semi-reflective reflector; 8. second semi-transparent and semi-reflective reflector; 9. shooting component; 10. light source; 11. fourth reflector; 12. focusing objective lens; 13. polyimide film; 14. stage. DETAILED DESCRIPTION
[0044] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] The present invention provides a method for inducing micro porous carbon springs by controlling local carbonization and stress caused by heat accumulation during femtosecond laser direct writing. Micro porous carbon springs with a length of centimeters can be prepared within a few seconds, and the preparation can be repeated, which is suitable for simple and efficient mass production.
[0046] like Figure 1 As shown, in some embodiments of the present invention, a micro-nano processing system for preparing a micro porous carbon spring is provided, the micro-nano processing system comprising a pulse laser 1, an energy attenuator 2, a first reflector 3, a polarization rotation mirror 4, a second reflector 5, a third reflector 6, a first semi-transparent semi-reflective reflector 7, a fourth reflector 11, a focusing objective lens 12, a stage 14 and a control component; a three-dimensional moving mechanism is provided below the stage 14, and the three-dimensional moving mechanism is electrically connected to the control component;
[0047] The laser light path emitted by the pulse laser 1 passes through the energy attenuator 2, the first reflector 3, the polarization rotation mirror 4, the second reflector 5, the third reflector 6, the first semi-transparent and semi-reflective mirror 7, the fourth reflector 11 and the focusing objective lens 12 in sequence, and is irradiated onto the stage 14.
[0048] In some implementation cases of the present invention, Figure 1As shown, the micro-nano processing system also includes a shooting component 9 (i.e., a CCD camera), a second semi-transparent and semi-reflective mirror 8 and a light source 10 (i.e., an LED light source); the second semi-transparent and semi-reflective mirror 8 is located between the first semi-transparent and semi-reflective mirror 7 and the lens of the shooting component 9, and the light source 10 is facing the second semi-transparent and semi-reflective mirror 8.
[0049] In some implementation cases of the present invention, a three-dimensional moving mechanism is provided under the stage, and the stage can be adjusted according to the position of the laser. During laser scanning, the stage is also moved by the three-dimensional moving mechanism at a preset scanning speed.
[0050] In some implementation cases of the present invention, the control component can use SCA control software to control the three-dimensional moving mechanism.
[0051] Example
[0052] The method for preparing the micro porous carbon spring provided in this embodiment comprises the following steps:
[0053] 1. Debugging micro-nano processing system
[0054] according to Figure 1 A beam of femtosecond laser is emitted by a pulsed laser, passes through an energy attenuator (energy attenuator), and then sequentially passes through the first reflector, the polarization rotator, the second reflector, the third reflector, the first semi-transparent and semi-reflective reflector, and the fourth reflector, and is focused by an objective lens and finally irradiated onto the stage.
[0055] The numerical aperture NA of the objective lens selected in this embodiment is 0.14, and the magnification is 5 times.
[0056] The laser parameter debugging method used in this embodiment is: the fixed parameters of the laser beam after being focused by the objective lens are designed to be a laser wavelength of 1028 nm, a pulse width of 190 fs, a repetition frequency of 200 kHz; and a laser power of 2000 mW.
[0057] 2. Install polyimide film and glass slide
[0058] The polyimide film is ultrasonically cleaned and then fixed on a glass slide (glass substrate); the glass slide is placed on an electric stage, the position is adjusted horizontally, and the stage adsorption device (such as a vacuum pump) is turned on to make the glass slide fit tightly against the stage.
[0059] The thickness of the polyimide film used in this embodiment is 100 μm, and the thickness of the glass slide is 1 mm.
[0060] 3. Focus the laser on the surface of the polyimide film
[0061] The femtosecond laser beam with adjusted parameters was focused on the surface of the polyimide film, and the three-dimensional moving mechanism controlled the movement of the stage for scanning. The scanning speed was 5 mm / s to obtain a micro porous carbon spring with a spiral structure.
[0062] The whole process of sample focusing can be monitored in real time by a CCD camera.
[0063] Experimental Example 1: Morphology and structural characterization of micro porous carbon springs prepared using different laser powers and scanning speeds
[0064] Using the preparation method of the above embodiment, micro porous carbon springs of different sizes were prepared by adjusting different laser powers and scanning speeds. Figure 2 As shown in Figure 2, the growth interval of the micro porous carbon spring is as follows: Figure 3 As shown in the figure, it can be seen that too low a heat level will result in the micro porous carbon springs not being able to grow out of the polyimide substrate, while too high a heat level will result in the helical structure not being able to form carbon fibers.
[0065] The minimum size of the micro porous carbon spring that can be prepared by the preparation method of the above embodiment is: diameter 755 μm, pitch 1210 μm, width 52 μm, thickness 26 μm; the corresponding laser parameters selected are: laser power 700 mW, scanning speed 5 mm / s. The maximum size of the micro porous carbon spring that can be prepared by the preparation method of the above embodiment is: diameter 1410 μm, pitch 1620 μm, width 130 μm, thickness 57 μm; the corresponding laser parameters selected are: laser power 4000 mW, scanning speed 5 mm / s.
[0066] In the growth range of micro porous carbon springs, the width, thickness, diameter and pitch of the micro porous carbon springs are proportional to the laser power and inversely proportional to the scanning speed. This is attributed to the significance of the thermal accumulation effect during laser scanning, which is proportional to the laser power and inversely proportional to the scanning speed.
[0067] The surface and cross-section of the micro porous carbon spring prepared in Example 1 were characterized by scanning electron microscopy. Figure 4 shown. Figure 4 a shows the microscopic morphology of a single micro porous carbon spring, which can be seen as a ribbon-like spiral structure. By observing the inner and outer surfaces of the micro porous carbon spring at a higher magnification, Figure 4 As shown in Fig. 4b and 4c, both the inner and outer surfaces of the micro porous carbon spring present a porous structure. The difference is that compared with the outer surface, the inner surface presents a thinner sheet structure with fewer and larger pores, while the outer surface has a thicker carbon wall, denser and smaller pores.
[0068] The micro porous carbon spring prepared in Example 1 was subjected to EDS analysis. Figure 5 Element distribution map of part of the micro porous carbon spring shown. Figure 5 The following are the local SEM image of the micro porous carbon spring (upper left), the local element distribution map of the micro porous carbon spring (upper right), the C element distribution map (lower left) and the O element distribution map (lower right). Figure 5 It can be seen that there are mainly C and O elements; among them, the C element occupies the entire structure, and the O element is only distributed on the surface of the structure, which comes from the adsorption of oxygen in the air, proving that the laser-induced microspring is a full-carbon structure.
[0069] The micro porous carbon spring prepared in Example 1 was analyzed by Raman spectroscopy. Figure 6 As shown, it can be seen that at 1350 cm -1 and 1580 cm -1 The presence of D peak and G peak nearby indicates that the main structure is amorphous carbon.
[0070] Experimental Example 2: Effects of processing parameters such as laser power and scanning speed on the dimensional parameters of micro porous carbon springs
[0071] The preparation method of Example 1 was used, and the power of the femtosecond laser was adjusted to 700 mW, 1000 mW, 1500 mW, 2000 mW, 2500 mW, 3000 mW, 3500 mW and 4000 mW, respectively, and the width, thickness, diameter and pitch of each prepared micro porous carbon spring were measured respectively. The results are as follows Figure 7-10 As shown, with the increase of laser power, the width, thickness, diameter and pitch of the micro porous carbon spring gradually increase until the polyimide film is ablated through.
[0072] The preparation method of Example 1 was used, and the scanning rates of the femtosecond laser were adjusted to 1 mm / s, 2 mm / s, 3 mm / s, 4 mm / s, 5 mm / s, 6 mm / s, 7 mm / s, 8 mm / s, 9 mm / s and 10 mm / s, respectively, and the width, thickness, diameter and pitch of each prepared micro porous carbon spring were measured respectively. The results are shown in FIG. Figure 11-14 As shown, with the increase of scanning speed, the width, thickness, diameter and pitch of the micro porous carbon spring gradually decrease until the accumulated heat is not enough to induce the generation of micro porous carbon springs on the surface of the polyimide film.
[0073] Based on the above test results, micro porous carbon springs were repeatedly induced using different processing parameters such as laser power and scanning speed, and characterized one by one to complete the statistics and summary of the size parameters and performance of micro porous carbon springs. The relationship between different processing parameters and the parameters of the prepared micro porous carbon springs was studied, and a micro-nano processing parameter database for femtosecond laser preparation of micro porous carbon springs was established.
[0074] Test Example 3: Mechanical Properties Test of Micro Porous Carbon Spring
[0075] The micro porous carbon spring prepared in Example 1 was subjected to a tensile test, and the results are as follows: Fig.15 As shown in the figure. Under a steady external force, the micro porous carbon spring is stretched from 26.1 mm in the natural state to a maximum of 43.5 mm, and the strain reaches 66.7%, indicating that the porous structure gives the micro porous carbon spring stretchability and can store a certain amount of elastic potential energy. The elastic constant of the micro porous carbon spring is about 1.2 N / m.
[0076] Experimental Example 4: Effect of the Thickness of Polyimide Film on the Size Parameters of Micro-porous Carbon Springs
[0077] The micro porous carbon spring selected in this test example was prepared by the method of the embodiment with the thickness of the polyimide film adjusted to 50-200 μm. Fig.16 As shown in Figure 2, when the thickness of the polyimide film is less than 50 μm, the laser will ablate through the film, and the gas produced during pyrolysis and carbonization is not sufficient to induce the formation of micro porous carbon springs on the surface of the polyimide film.
[0078] Test Example 5: Conductive Performance Test of Micro-porous Carbon Spring
[0079] The resistance test of the micro porous carbon spring prepared in the embodiment is carried out, and the results are as follows: Fig.17 The length of the carbon spring is about 1 cm. The resistance of the carbon spring prepared under the laser parameters is measured by using a UT890D digital multimeter to be 16.8 kΩ. This indicates that the micro porous carbon spring prepared by the preparation method of the present invention has good electrical conductivity.
[0080] After further experiments, a simple circuit was prepared using the carbon spring as a wire, which could light up an LED lamp when connected to a 3 V DC power supply.
[0081] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A method for preparing a micro porous carbon spring based on femtosecond laser micro-nano processing, characterized in that: The method comprises the following steps: fixing a polyimide film on a glass slide, and fixing the glass slide on a stage; adjusting laser parameters, focusing a laser beam on the surface of the polyimide film for scanning, and obtaining the micro porous carbon spring; the laser parameters are laser power of 500 mW-4000 mW and scanning speed of 1-10 mm / s.
2. The method for preparing a micro porous carbon spring based on femtosecond laser micro-nano processing according to claim 1, characterized in that: The numerical aperture NA of the objective lens is 0.14, and the magnification is 5 times; the method for debugging the laser parameters is as follows: the fixed parameters of the laser beam after being focused by the objective lens are designed to be a laser wavelength of 1028 nm, a pulse width of 190 fs, and a repetition frequency of 200 kHz.
3. The method for preparing a micro porous carbon spring based on femtosecond laser micro-nano processing according to claim 1, characterized in that: The thickness of the polyimide film is 50-200 μm.
4. The method for preparing a micro porous carbon spring based on femtosecond laser micro-nano processing according to claim 3, characterized in that: The thickness of the polyimide film is 100 μm.
5. The method for preparing a micro porous carbon spring based on femtosecond laser micro-nano processing according to claim 1, characterized in that: The scanning speed is 5 mm / s.
6. A micro porous carbon spring prepared by the preparation method according to any one of claims 1 to 5.
7. An application of the micro porous carbon spring according to claim 6, characterized in that: Used to manufacture micro-mechanical equipment and micro-electronic components.
8. A micro-nano processing system for preparing micro porous carbon springs, characterized in that: The micro-nano processing system comprises a pulse laser, an energy attenuator, a first reflector, a polarization rotator, a second reflector, a third reflector, a first semi-transparent semi-reflective reflector, a fourth reflector, a focusing objective lens, a stage and a control component; a three-dimensional moving mechanism is provided below the stage, and the three-dimensional moving mechanism is electrically connected to the control component; The laser light path emitted by the pulse laser passes through the energy attenuator, the first reflector, the polarization rotation mirror, the second reflector, the third reflector, the first semi-transparent and semi-reflective mirror, the fourth reflector and the focusing objective lens in sequence, and is irradiated onto the stage.
9. The micro-nano processing system for preparing micro porous carbon springs according to claim 8, characterized in that: It also includes a shooting component, a second semi-transparent and semi-reflective mirror and a light source; the second semi-transparent and semi-reflective mirror is located between the first semi-transparent and semi-reflective mirror and the lens of the shooting component, and the light source faces the second semi-transparent and semi-reflective mirror.
10. A micro-nano processing parameter database for preparing micro porous carbon springs, characterized in that: The micro-nano processing parameter database is constructed by setting different laser parameters to obtain corresponding micro porous carbon springs, and testing to obtain the diameter, thickness, width and pitch of the micro porous carbon springs.
Citation Information
Patent Citations
Sensing element and elastic sensitive element processing integrated sensor and preparation method thereof
CN109781151A
Preparation method and device of long-period fiber bragg grating with graphene coating
CN111175872A
System and method for processing nanometer protrusion structure on titanium surface through femtosecond laser
CN113102892A
Composite material surface microstructure preparation method based on laser diffraction effect
CN113146028A
Micropore processing method of upper die for laminating thin film sheet by using femtosecond laser
CN115890022A
Cited By
Femtosecond laser preparation method and application of zinc negative electrode PVA-porous carbon array protective layer
CN121662759A
A femtosecond laser preparation method of a zinc negative electrode PVA-porous carbon array protective layer and application thereof
CN121662759B